Cross-Sectional Analysis of Probable Causative Factors Leading to Iron Deficiency Anemia in Primigravida During Their First Trimester: Iron Deficiency Anemia in Primigravida During Their First Trimester - Altaf, Aisha; Baloch, Falak Naz; Ilyas, Shahla; Ali, Abrar; Zuberi, Nadeem; Punar, Zakir Ali; Unar, Laraib (Pakistan Journal of Health Sciences, 2025)
Anemia is a common nutritional deficiency that impacts approximately 1.6 billion individuals globally, representing around 25% of the world’s population. Objectives: To assess the prevalence of factors associated with anemia due to iron deficiency in primigravida females during their first trimester. Methods: A descriptive, cross-sectional study was conducted at Agha Khan University Hospital, Karachi, from January 4 to July 3, 2019. The study aimed to screen pregnant women during their first antenatal visit in the Outpatient Department for eligibility based on the inclusion criteria. Data were recorded using a structured proforma. Effect modifiers were controlled by stratifying age in years and gestational age in weeks, with comparisons between stratified groups made using Chi-square analysis. Results: Mean ± SD of age and gestational age in primigravida females was 27.50 ± 5.36 years and 7.93 ± 2.07 weeks, respectively. Mean ± SD of height, weight and BMI was 156.44 ± 5.81 cm, 65.90 ± 10.84 kg and 28.84 ± 4.10 kg/m2, respectively. In frequency of associated factors, advanced maternal age was found to be responsible for iron deficiency anemia in 27 (55.10%) women, underweight in 2(4.08%), low educational status in 7 (14.28%) and low socioeconomic status was 13 (26.53%) women. Conclusions: It was concluded that in the Pakistani population, the prevalence of iron deficiency anemia is high among pregnant women. Maternal anemia is significantly linked to maternal age and low socioeconomic status. The results emphasize the critical need to raise awareness among pregnant women and their families regarding the significance of antenatal care.